Protocol to study ischemic stroke by photothrombotic lesioning in the cortex of non-human primates - Noah Stanis; Karam Khateeb; Jasmine Zhou; Ruikang K. Wang; Azadeh Yazdan-Shahmorad (STAR Protocols, 2023)
Summary: Neurorehabilitation strategies for ischemic stroke have shown promise for functional recovery, yet minimal tools are available to study rehabilitation techniques in non-human primates (NHPs). Here, we present a protocol to study rehabilitation techniques in NHPs using a photothrombotic technique, a form of optical focal lesioning. We also describe steps for simultaneous neurophysiological recording and in vivo validation through vascular flow imaging. This interface can examine emerging neurorehabilitation strategies in the post-stroke environment in NHPs that are evolutionarily close to humans.For complete details on the use and execution of this protocol, please refer to Khateeb et al. (2022).6 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.